2009
DOI: 10.1667/rr1570.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Expression Profiles of Several Fibroblast Growth Factor Receptors in the Mouse Jejunum: Suggestive Evidence for a Differential Radioprotective Effect among Major FGF Family Members and the Potency of FGF1

Abstract: Several members of the fibroblast growth factor (FGF) family have the potential to protect the intestine against the side effects of radiation therapy. FGF1 is capable of signaling through all subtypes of FGF receptors (FGFRs), whereas FGF7 and FGF10 activate only the epithelial-specific subtype, FGFR2IIIb (FGFR2b). The present study compared the protective activity of FGF1, FGF7 and FGF10 and examined the profiles of FGFR expression in the jejunum of BALB/c mice given total-body irradiation (TBI) with gamma r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…As a multifunctional calcium/phosphate-regulating hormone, 1,25(OH) 2 D 3 exerts a plethora of genomic and nongenomic actions in the small intestine to increase calcium and phosphate Consistent with previous reports of FGFR expression in the small intestine, i.e., the duodenum and jejunum (16,39), the present immunohistochemical analyses showed FGFR 1-4 protein expression in the basolateral membrane of duodenal villous epithelial cells, thus confirming that these 1,25(OH) 2 D 3 -responsive duodenal cells acted as targets of FGF-23. Indeed, FGFR proteins were also observed in other duodenal cell compartments, i.e., cytoplasm and apical membrane, but their function is not well understood.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As a multifunctional calcium/phosphate-regulating hormone, 1,25(OH) 2 D 3 exerts a plethora of genomic and nongenomic actions in the small intestine to increase calcium and phosphate Consistent with previous reports of FGFR expression in the small intestine, i.e., the duodenum and jejunum (16,39), the present immunohistochemical analyses showed FGFR 1-4 protein expression in the basolateral membrane of duodenal villous epithelial cells, thus confirming that these 1,25(OH) 2 D 3 -responsive duodenal cells acted as targets of FGF-23. Indeed, FGFR proteins were also observed in other duodenal cell compartments, i.e., cytoplasm and apical membrane, but their function is not well understood.…”
Section: Discussionsupporting
confidence: 91%
“…In other words, besides being a phosphatonin, FGF-23 may also act as a calcium-regulating hormone to modulate intestinal calcium absorption. In addition to its indirect action by lowering plasma 1,25(OH) 2 D 3 levels, we hypothesized that FGF-23 could directly regulate calcium transport in intestinal epithelial cells, which have been reported to express FGFR mRNA (16).…”
mentioning
confidence: 99%
“…The molecular mechanism underlying the ability of FGF15/19 to regulate intestinal CYP3A expression will be an important topic for future studies. In that regard, the effects of FGF15/19 on hepatic CYP7A1 expression are mediated at least partly through the fibroblast growth factor receptor 4 and b-Klotho, which are also expressed in the mouse SI (Sinha et al, 2008;Hagiwara et al, 2009). Additionally, although the primary function of FGF15/ 19 in the adult is to regulate BA homeostasis in an endocrine fashion, FGF15/19 also plays a role in controlling energy homeostasis via activation of the extracellular signalregulated kinase signaling pathway and inactivation of the transcription factor cAMP regulatory element-binding protein (Potthoff et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that among the wild-type FGFs examined (FGF1, FGF7 and FGF10), FGF1 exerts the strongest protective effect against radiation-induced injury of small intestine crypts, the intestinal epithelial stem cell niche. 59,60) Strong gamma or X-ray radiation causes death of the irradiated animals within days, mainly due to failure of the regeneration of the intestinal epithelial cells. Using this assay system, we assessed the protective effects of FGFC and found that when 10 µg of FGFC or FGF1 were intraperitoneally administered to BALB/c mice 24 h before administration of 10 Gy of whole body γ-irradiation, the crypt survival after 3.5 d was significantly greater than in control mice receiving saline.…”
Section: )mentioning
confidence: 99%